Understanding the Role of Vaping in Criminal Behavior Among Adolescents. (September 2022) - Vito, Anthony G.; Rocheleau, Gregory C.; Intravia, Jonathan
This study examines the link between ever vaped, vaped just flavoring in the past 30 days, and vaped just flavoring frequently in the past 30 days and violent crime, property crime, marijuana use, and smoking. Using the 2017 Monitoring the Future form two data set and propensity score matching, the researchers are better able to consider the impact of the vaping behavior among similarly situated 12th-grade adolescents. Results illustrate that there are no vaping behaviors linked with violent crime or property crime among similarly situated adolescents. In contrast, results show that adolescents who have ever vaped, vaped just flavoring, or vaped just flavoring frequently are linked with marijuana use and smoking. Limitations and future research implications are discussed.